2005
DOI: 10.1007/s00726-005-0158-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic glutamate administration to pregnant rats during gestation on metabotropic glutamate receptors from mothers and full-term fetuses brain

Abstract: Chronic glutamate treatment during gestational period caused a significant decrease in total metabotropic glutamate receptors (mGluR) number. Similar results were observed on the steady-state level of mGlu(1) receptor detected by immunoblotting assays, suggesting that this is the main receptor subtype modulated by agonist exposure. Furthermore, no variations on mRNA coding mGlu(1) receptor were found, suggesting post-transcriptional modulation as a possible mechanism of the lost of receptor detected at the mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
3
6
0
Order By: Relevance
“…The down‐regulation of mGlu reported in this work in maternal brain could be, therefore, a response to receptor overstimulation evoked by excessive glutamate release. This is in agreement with previous studies showing the down‐regulation of mGlu 1 or mGlu 5 receptors caused by a prolonged treatment with mGlu receptor agonists in C6 glioma cells (Albasanz et al, 2002) and astrocytes (Balazs et al, 1997) and in vivo when glutamate is chronically consumed during gestation (León Navarro et al, 2005). The results obtained by Western blot suggest that both mGlu 1 and mGlu 5 receptors are down‐regulated in response to chronic R‐PIA treatment in maternal brain, which agrees with the decrease of specific binding of [ 3 H]quisqualic acid in plasma membranes from gestant rats treated with R‐PIA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The down‐regulation of mGlu reported in this work in maternal brain could be, therefore, a response to receptor overstimulation evoked by excessive glutamate release. This is in agreement with previous studies showing the down‐regulation of mGlu 1 or mGlu 5 receptors caused by a prolonged treatment with mGlu receptor agonists in C6 glioma cells (Albasanz et al, 2002) and astrocytes (Balazs et al, 1997) and in vivo when glutamate is chronically consumed during gestation (León Navarro et al, 2005). The results obtained by Western blot suggest that both mGlu 1 and mGlu 5 receptors are down‐regulated in response to chronic R‐PIA treatment in maternal brain, which agrees with the decrease of specific binding of [ 3 H]quisqualic acid in plasma membranes from gestant rats treated with R‐PIA.…”
Section: Discussionsupporting
confidence: 93%
“…Total RNA was isolated by guanidium thiocyanate/phenol/chloroform extraction following the method of Chomczynski and Sacchi (1987). RT‐PCR assays were performed as described by León Navarro and coworkers (2005) using the primers 5′‐AAATCTACAGCAATGCTGGCGA‐3′ and 5′‐CTTCGATGACTTCATCTCTGT‐3′ for mGlu 1 receptor, 5′‐TGAAAGAAGATGTACGAGGGAGTG‐3′ and 5′‐TTT CTTGGAGCGGAAGGAAGAAG‐3′ for mGlu 5 receptor, 5′‐GAGAACCGAATGGAGGAGAGCAA‐3′ and 5′‐GTCCAC GAACATCTTCAGGATGAA‐3′ for αG q/11 , and 5′‐TTT TCGGCAGACCGGAAGCGA‐3′ and 5′‐TGCTGTTGG GCTCGTACTTCT‐3′ for PLCβ 1 . PCR products were analyzed by electrophoresis in 2% agarose gels and stained with ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%
“…2002). However, as recently described, we did not detect significant variation in either food intake or weight gain of animals (León Navarro et al. 2005).…”
Section: Resultssupporting
confidence: 82%
“…In the present work, we have shown that chronic glutamate intake during pregnancy induces a down‐regulation of αGi 3 . A possible explanation may be drawn from a previous work in which the effect of chronic glutamate administration during gestation on metabotropic glutamate receptors from maternal and full‐term fetal brains was studied (León Navarro et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation